Architectural Theorisations and Phenomena in Asia : The Polychronotypic Jetztzeit - Lin, Francis Chia-Hui (Springer International Publishing : Imprint: Palgrave Macmillan, 2017)
This book is the first overall and detailed discussion of contemporary Asia's architectural theorisations and phenomena based on its heteroglossic and decolonisation character. Lin presents a theoretical journey of transdisciplinary reflection upon contemporary Asia's pragmatic phenomena which is methodologically achieved by means of elaborations of how tangible Asian architecture can be philosophically theorised and how interchangeable architectural theory is practically 'Asianised'. Discussions in the book are critically integrated with comparative studies focused on Japan, Taiwan, China, Hong Kong, Singapore, Malaysia, Australia, New Zealand and the UK. These empirical examinations are highlights of phenomenal localities, architecture, cities and cultures which reference the historicity of the Asia Pacific, Asia's contemporary architectural situations, and their subtle relationship with the 'West'. The schematisation of intended 'fuzziness' for Asia and its architecture is framed as the notion polychronotypic jetztzeit to represent a present time-place context of contemporary Asian architecture and urbanism. This book will be of great interest to scholars of Asian Studies, Architectural Studies, Postcolonial Studies, Urban Studies and Cultural Studies.
Keywords: Social sciences.; Urban geography.; Urban planning.; City planning.; Area studies.; Religion and culture.; Sociology, Urban.; Human geography.; elektronické knihy; electronic books